Financial Literacy, Experimental Preference Measures and Field Behavior – A Randomized Educational Intervention - Matthias Sutter; Michael Weyland; Anna Untertrifaller; Manuel Froitzheim; Sebastian O. Schneider (Center for Economic Studies and ifo Institute (CESifo), 2023)
We present the results of a randomized intervention to study how teaching financial literacy to 16-year old high-school students affects their behavior in risk and time preference tasks. Compared to two different control treatments, we find that teaching financial literacy makes subjects behave more patiently, more time-consistent, and more risk-averse. These effects persist for up to almost 5 years after our intervention. Behavior in the risk and time preference tasks is related to financial behavior outside the lab, in particular spending patterns. This shows that teaching financial literacy affects economic decision-making which in turn is important for field behavior.
Keywords: C93; D14; I21; 330; financial literacy; randomized intervention; risk preferences; time preferences; financial behaviour; field experiment